SWOT ANALYSIS OF CREATIVE STARTUPS IN THE CHEMICAL AND PHARMACEUTICAL INDUSTRIES - Sukma, Rimba Krisnha; Amir, Syafiq; Huda, Nurul (Journal of Social Entrepreneurship and Creative Technology, 2025)
The chemical and pharmaceutical industries, while traditionally dominated by large corporations, have seen a rise in creative startups that introduce innovative products, technologies, and business models. These startups often face unique challenges due to high barriers to entry, regulatory constraints, and the need for substantial investment in research and development. However, they also possess distinctive advantages, such as flexibility, agility, and the ability to drive innovation. This research aims to conduct a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis of creative startups within the chemical and pharmaceutical industries, to better understand the factors that influence their success and sustainability. The study uses a mixed-methods approach, combining qualitative case studies with quantitative data from industry reports and surveys. The findings indicate that while these startups often excel in innovation and product differentiation, they struggle with scaling, navigating regulatory challenges, and securing funding. Despite these challenges, opportunities exist in niche markets, partnerships with established firms, and emerging trends in sustainable practices and biotechnology. The study concludes that creative startups in the chemical and pharmaceutical sectors can succeed by leveraging their strengths in innovation and collaboration while addressing weaknesses through strategic investment and regulatory compliance.